Mitos sobre el estreñimiento - Wendy J. Dahl (EDIS)
This 2-page Spanish-language fact sheet addresses common myths about constipation. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.